Analisis Gaya Belajar Siswa Berprestasi Kelas IV SDN 51 Banda Aceh - Maulisa, Risma; Mislinawati, Mislinawati; Vitoria, Linda (Universitas Syiah Kuala, 2024)
As we know, every child is born with different abilities, characteristics and various backgrounds, which results in different learning styles and the level of students' abilities in the material presented also varies. One of the student characteristics related to absorbing, processing and conveying information is the student's learning style. Each student has their own learning style, this learning style is the medium for students to understand the material presented by the teacher, for this reason teachers are also required to be able to understand each student's learning style, in order to minimize failure in learning. The aim of this research is to analyze the learning styles of class IV achieving students at SDN 51 Banda Aceh. This research is qualitative research with a descriptive research type. The data sources in this research were class IVA and class IVB students. The data collection techniques used were observation and questionnaires with 30 items of learning style statements in observation and 45 items of learning style statements in the questionnaire. The data obtained was then analyzed using qualitative data analysis techniques, namely data reduction (Data Reduction), data presentation (Data Display) and data conclusion/verification (Conclusion Drawing/Verification) as well as questionnaire calculations using Gutman Scale calculations. Based on the results of data analysis, it can be concluded that the outstanding students in class IV at SDN 51 Banda Aceh show a combination of VAK learning styles, (Visual, Auditorial and Kinesthetic). High achieving students learn through visual, auditory, and kinesthetic processes in the classroom. Learn through visuals during the teaching and learning process, students record material and read books. Auditory, during the teaching and learning process, students listen, listen to the teacher's explanation and discuss. Kinesthetic in the teaching and learning process, students often do light physical activities such as twirling pens, swinging chairs and tapping on tables. VAK learning style tendencies among high achieving students vary. Of the outstanding students in class IV at SDN 51 Banda Aceh, there is a tendency towards learning styles, namely: 4 outstanding students who tend to use a visual learning style with a visual auditory kinesthetic portion; while 14 students tend to have an auditory learning style with an auditory visual kinesthetic portion, and only 2 high achieving students tend to have a kinesthetic learning style with a kinesthetic visual auditory portion.